Urgensi Strategi Guru dalam Mengelola Kelas terhadap Keefektifan Pembelajaran PAI di SMU Negeri 1 Cina (Studi Kasus di SMU Negeri 1 Cina Kab. Bone) - Supriadi (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
This research is intended to find out the urgency of strategies teachers manage classroom learning effectiveness against PAI at SMU Negeri 1 China Excl. The Chinese Government. Bone, with the problem of how the learning process PAI at SMU Negeri 1 China Excl. The Chinese Government. Bone and what strategies do the guru PAI in streamline the learning process at SMU Negeri 1 China Excl. The Chinese Government. Bone.The type of research conducted in this thesis is descriptive qualitative approach with verifikatif, which means research that intends to describe the situation and events in the sense accumulates basic data are the descriptive i.e. urgency strategies teachers manage classroom learning effectiveness against PAI at SMU Negeri 1 China Excl. The Chinese Government Bone.From the results of the analysis and discussion of the research that the teaching and learning process at SMU Negeri 1 China Excl. The Chinese Government. Bone went smoothly because of the power his tutor had been complying with the rules and methods in teaching and learning. While the urgency of managing class teacher strategies against the effectiveness of learning PAI at SMU Negeri 1 China is very urgent in PAI learning, so it is the responsibility of the teacher in the learning of PIE it is desirable so that programs can be running smoothly.